Patty's industrial hygiene. Volume 1, - Cohrssen, Barbara (John Wiley & Sons, Inc., 2021)
"Since the first edition in 1948, Patty's Industrial Hygiene and Toxicology has become a flagship publication for Wiley. During its nearly seven decades in print, it has become a standard reference for the fields of occupational health and toxicology. The volumes on industrial hygiene are cornerstone reference works for not only industrial hygienists but also chemists, engineers, toxicologists, lawyers, and occupational safety personnel. Volume 1 covers Introduction of Industrial Hygiene and Recognition of Chemical Agents. In addition to revised and updated chapters, a number of new chapters reflect current technology and concerns. The chapters include Ethics in Industrial Hygiene, Prevention through Design, Risk Communication, Managing Workplace Demographics, and Mastering Digital Media for Workers, Employers and Community Practice."
Keywords: Industrial hygiene.; Industrial toxicology.; elektronické knihy; electronic books